Analysis of Mathematical Communication Skills Reviewed from Self-Efficacy - Budi Wahyu Pertiwi; Helmy Wahyu Widiarti; Gunawan Gunawan; Anton Jaelani (STKIP Singkawang, 2025)
Effective mathematical communication plays a crucial role in the resolution of mathematical problems. Despite efforts to enhance mathematical communication, the success rate among students remains relatively low, a situation that is closely associated with their levels of self-efficacy. The purpose of the study was to describe students' mathematical communication skills based on self-efficacy. The research adopts a descriptive qualitative method. The subjects of this study consisted of seventh-grade students who had studied the material on flat shapes. According to the outcomes of the self-efficacy questionnaire, students are classified into three categories: high, medium, and low. Each category was taken by one student as a respondent with the purposive sampling technique. Data collection techniques include tests, questionnaires, and interviews. Data analysis techniques include data reduction, data presentation, and conclusion. The analysis indicated that students exhibiting higher levels of self-efficacy displayed enhanced mathematical communication skills when compared to their peers who possessed lower levels of self-efficacy. This study revealed a significant relationship between mathematical communication and self-efficacy. Students with elevated levels of self-efficacy display enhanced proficiency in mathematical communication skills in comparison to their peers who possess medium and low levels of self-efficacy.